IMPLIKASI HUKUM PERJANJIAN ELEKTRONIK DALAM TRANSAKSI BISNIS DIGITAL DI ERA EKONOMI BERBASIS PLATFORM: ANALISIS TERHADAP VALIDITAS DAN RISIKO HUKUM - Henrikus Renjaan (PATRIOT, 2025)
Advances in information technology have driven a shift from conventional digital-based transactions to electronic agreements (e-contracts). This phenomenon has created new dynamics in contract law practices, particularly in the realm of platform-based e-commerce platforms such as Tokopedia and Shopee. This study aims to analyze the validity and legal risks of e-contracts based on the provisions of the Civil Code and Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), and to assess the effectiveness of legal protection for consumers and businesses. The method used is normative legal research with a regulatory, conceptual, and case-based approach. Data were qualitatively reviewed through literature and legal documents, and systematically analyzed based on classical contract theory and the principle of contractual justice. The results indicate that, from a formal legal perspective, e-contracts have binding force and guarantee compliance with the requirements for a valid agreement under Article 1320 of the Civil Code and the principles of the ITE Law. However, in practice, various legal issues are encountered, such as breach of contract, exclusion clauses, unequal positions of parties, and difficulties in providing evidence, which are detrimental to consumers. Digital platforms tend to position themselves as neutral parties, even though they play a crucial role in transaction mechanisms. Therefore, stricter regulations regarding platform responsibility, transparency of clauses, and strengthening of the settlement system through Online Dispute Resolution (ODR) mechanisms are needed. This study recommends improving digital legal literacy, reformulating electronic contract regulations, and equitable law enforcement as strategies for balanced legal protection in the digital economy era.